Role of Hydration in Biomembranes as a Challenge for Current Biophysics - Disalvo, Edgardo Anibal (2021)
The consideration of water as a structural component gives biological membranes specific thermodynamic properties that explain its responsive behavior when chased by physical and chemical perturbations. These properties are derived from the peculiar surface tension of pure water and its variation due to the presence of hydrogen bonds arrangements between water and membrane components that determine a complex surface free energy profile. A completer and more realistic picture should consider how the hydration properties are linked to mechanical forces with relevance in osmotic stress of cells and in the behavior lipid monolayers. In the present work, the mechano-chemical coupling of surface pressure with water activity in a lipid interphase is explored as a way to mimic the thermodynamic response of the lipid interphase to bioactive compounds. As a result, the relaxation processes during the action of bio effectors are described in terms of water organization around the lipid residues such as acyl chains and polar head groups.